Emerging Roles for NLRC5 in Immune Diseases - Wang, Jie-quan; Liu, Ya-ru; Xia, Quan; Chen, Ruo-nan; Liang, Jun; Xia, Qing-rong; Li, Jun (Frontiers in Pharmacology, 2019)
Innate immune activates the corresponding immune response, requiring identification of pathogens by multiple pattern recognition receptors (PRRs), like NOD-like receptors (NLRs). To our knowledge, NLRs are a large protein family of pattern recognition receptors in the cytoplasm, which involved in inflammatory diseases and promoted the rapid clearance of invasive pathogens. Additionally, NLRC5 is the largest member of NLRs, participating in immune responses repeatedly. Notably, the expression of NLRC5 increased significantly in immune cells and immune-related tissues. Nevertheless, the evidence for higher expression of NLRC5 in immune disease is inconsistent. Furthermore, there is growing evidence that NLRC5 was involved in the innate immune response and inflammatory diseases. NLRC5 has been confirmed to exert a critical role in the control of regulatory diverse signaling pathways. In particular, NLRC5 broadly participated in the occurrence and development of immune diseases, which is a potential therapeutic target. However, in order to develop targeting drugs, a more profound understanding of intrinsic characteristic and underlying mechanisms of NLRC5 is necessary. Herein, current knowledge of NLRC5 is summarized, and research advances of NLRC5 in the characteristic, biological function and regulation mechanisms are reviewed.